Map showing line of Newfoundland railway and steamship lines [between 1905 and 1911?] - Newfoundland Railway Company ([St. John's], 1905)
Black and white. Relief shown by hachures and spot heights. Bar scale in miles. Shows rail and steamship lines. Includes ancillary map: Newfoundland map shewing [sic] line of Newfoundland Railway. Semi-annual publication.